Forty Years of Struggle and Still no Right to Inuit Education in Nunavut - Derek Rasmussen (2011)
Describes 40 (now 50) years of Inuit advocacy and attempts to change Qalunaat colonial education system to an Inuit-language K-12 education system that reflects Inuit values. Documents moves made by majority non-Inuit managers in the public government to prevent & obstruct Inuit language education.